2017
DOI: 10.1177/2055217317717508
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and neuropsychiatric disorders among MS patients from Latin America

Abstract: Cognitive and neuropsychiatric disorders in patients with multiple sclerosis have been extensively documented. The focus of this review will be on cognitive and neuropsychiatric disorders in multiple sclerosis patients from Latin America, in the context of international literature. Multicentre studies carried out in Latin America have shown that 43% of the patients have cognitive impairment and 34.5% in early stages of the disease, 29% depression and 20.9% neuropsychiatric disorders. The profile of cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 78 publications
0
5
0
1
Order By: Relevance
“…Other epidemiological studies reported frequencies of cognitive impairment in patients with MS between 40–70% in North America and Europe [19]. Frequencies of 40–60% have been reported in Latin America [20]. Even though a variety of different methodological approaches and neuropsychological batteries have been used, results are very similar across all reported populations.…”
Section: Cognitive Impairment In Multiple Sclerosismentioning
confidence: 75%
“…Other epidemiological studies reported frequencies of cognitive impairment in patients with MS between 40–70% in North America and Europe [19]. Frequencies of 40–60% have been reported in Latin America [20]. Even though a variety of different methodological approaches and neuropsychological batteries have been used, results are very similar across all reported populations.…”
Section: Cognitive Impairment In Multiple Sclerosismentioning
confidence: 75%
“…Moreover, another disabling consequence of MS is cognitive impairment (CI). This can affect 40-70% of patients at any time throughout disease progression ( 10 , 11 ). Attention, working memory and executive function are commonly affected in patients with MS ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other psychiatric manifestations have a lower prevalence in MS. Emotional incontinence, characterised by uncontrollable episodes of laughing and crying, has been reported in about 10% of PwMS 10. It is due to a dissociation from the underlying emotional experience, thus resulting in incongruent emotional expression.…”
Section: Prevalence Clinical Characteristics and Impact Of Psychiatri...mentioning
confidence: 99%